Industrial Heritage: Atarazanas Market’s squares in Málaga - Palomares Alarcón, Sheila (2014)
This abstract tries to make known one of the first attempts to recuperate the buildings heritage at the end of the 19th century in Spain: It’s called Atarazanas Market’s squares in Málaga, a marvellous Joaquín Rucoba’s architect work. It is one of the first examples in iron architecture in Spain which opted preservation building heritage from the respect of the place memory even in his last restoration.